Human papillomavirus and surgical smoke: a systematic review. (8th May 2020) - Fox-Lewis, Andrew; Allum, Caroline; Vokes, David; Roberts, Sally
Abstract : Objective: To evaluate what is currently known about the risk to surgeons and other operating theatre (OT) staff of human papillomavirus (HPV) transmission and HPV-related disease following surgical smoke exposure. Methods: A systematic literature search of Embase and Ovid-MEDLINE was undertaken for primary studies relevant to the presence of HPV in surgical smoke, contamination of OT staff with HPV after performing or attending smoke-generating surgical procedures, and the presence of HPV or HPV-related disease in OT staff following occupational surgical smoke exposure. Additional articles were identified by searching the reference lists of relevant published papers. Results: Twenty-one relevant articles were identified. These demonstrate that surgical smoke from the treatment of HPV-related lesions can contain HPV DNA, and that this can contaminate the upper airways of OT staff. Whether this corresponds to infectious virus is not known. Increased prevalence of HPV infection or HPV-related disease in OT staff following occupational exposure to surgical smoke has not been convincingly shown. Conclusions: While HPV transmission to OT staff from surgical smoke remains unproven, it would be safest to treat surgical smoke as potentially infectious. Necessary precautions should be taken when performing smoke-generating procedures, consisting of: (1) local exhaust ventilation, (2) general room ventilation and (3) full personal protective equipment including a fit tested particulate respirator of at least N95 grade. There is currently insufficient evidence to recommend HPV vaccination for OT staff or to state that the above precautions, when used properly, would not be effective at preventing HPV transmission from surgical smoke.